Model Problem Based Learning dengan Strategi Scaffolding untuk Meningkatkan Prestasi Belajar Matematika Siswa - Putri, Febriana Mulyana; Buchori, Achmad; Ariyanto, Lilik; Ernawati, Isnaeni (Program Studi Pendidikan Matematika, FKIP, Universitas Siliwangi, Tasikmalaya, 2024)
This research aims to improve students' mathematics learning achievement through the Problem Based Learning model with the Scaffolding strategy. The type of research conducted by researchers is Classroom Action Research which is carried out in four stages (planning, implementing, observing, and reflecting) which adapts the Kemmis and McTaggart models. The subjects of this research were 35 students of class X Fashion SMK N 6 Semarang. The instruments used in collecting data consisted of observation sheets and tests. The results showed that the Problem Based Learning model with the Scaffolding strategy could improve students' mathematics learning achievement. This is evidenced in the first cycle the class average value was 72. In the second cycle there was an increase in the class average value of 76. The number of students who reached the completion limit in the first cycle was 24 students or 69%, while in the second cycle the number of students who reaching the completion limit of 27 students or 77% (an increase of 8%). Thus, it can be concluded that the application of the Problem Based Learning model with the Scaffolding strategy can improve students' Mathematics learning achievement.Keywords: Problem Based Learning; Scaffolding; Mathematics Learning Achievement